Innovations in Macroeconomics - Welfens, Paul J. J. (Springer, 2012)
Modern macroeconomics suffers from an unclear link between short-term Keynesian analysis and long-term growth modelling. This book presents a new link between monetary analysis and growth modelling in open economies. Structural change, innovations and growth are considered from a new perspective. With respect to economic policy - in particular innovation policy - the analysis implies major changes, concerning both EU countries and other leading OECD economies.